2016
DOI: 10.2174/1567205013666151116141416
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and Subcortical Changes in Alzheimer's Disease: A Longitudinal and Quantitative MRI Study

Abstract: Quantitative MRI provides important information about tissue properties in brain both in normal ageing and in degenerative disorders. Although it is well known that those with Alzheimer's disease (AD) show a specific pattern and faster rate of atrophy than controls, the precise spatial and temporal patterns of quantitative MRI in AD are unknown. We aimed to investigate neuroimaging correlates of AD using serial quantitative MRI. In our study, twenty-one subjects with AD and thirty-two similar-aged healthy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 29 publications
6
11
0
Order By: Relevance
“…The inconsistencies between the previous and current studies could possibly be explained by group sizes with in the current study, the number of cases being larger. A significant reduction in the level of SIRT1 protein was observed in AD and this is most likely explained by the greater degree of cortical atrophy seen in AD and the loss of neuronal or synaptic SIRT1 [35]. To further assess the role of SIRT1, activity was measured and compared to control, with SIRT1 activity reduced in all disease groups although no significant difference was seen between disease groups.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistencies between the previous and current studies could possibly be explained by group sizes with in the current study, the number of cases being larger. A significant reduction in the level of SIRT1 protein was observed in AD and this is most likely explained by the greater degree of cortical atrophy seen in AD and the loss of neuronal or synaptic SIRT1 [35]. To further assess the role of SIRT1, activity was measured and compared to control, with SIRT1 activity reduced in all disease groups although no significant difference was seen between disease groups.…”
Section: Discussionmentioning
confidence: 99%
“…For example, important differences in the characteristics of plaques in human AD and APP/PS1 mice may provide different mechanisms of MR contrast changes: plaques in APP/PS1 mice contain less iron, but are more densely packed compared with human AD samples [53]. Using voxel-based quantification, Su et al found that AD was characterised by reduced T 1 values in certain brain regions, including bilateral temporal and parietal lobes in cross-sectional comparison, and an increase in T 1 in the right caudate, bilateral hippocampus, parahippocampus, and thalamus in longitudinal comparison [20]. Increased T 1 values in white matter of AD patients has been reported [54], and taken together this demonstrates the complex nature of T 1 changes in the human AD brain.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional analysis of 21 subjects with AD and 32 similarly aged healthy controls, AD was characterised by reduced quantitative T 1 and T 2 values [20]. In previous work by the same authors, decreased T 1 values were found in patients with dementia with Lewy bodies compared with control subjects, highlighting the potential of T 1 measures in general to detect changes caused by neurodegeneration [21].…”
Section: Introductionmentioning
confidence: 99%
“…A primary limitation of postmortem studies is the inability to perform longitudinal assessment of regional brain atrophy in individual patients. Conventional MRI studies using cortical volumetric analysis have provided significant insight into longitudinal changes in regional atrophy associated with different subtypes of dementia [84][85][86]. We have shown that our in vivo technique with ultra-high field MRI can be used for similar studies of midbrain nuclei in PD.…”
Section: Future Directionsmentioning
confidence: 95%